(untitled) (Journal of Universal Science Research, 2023)
In the article of Family business and small business and entrepreneurship development some aspects in particular word is conducted. ensuring the stability of the family economy through the development of entrepreneurship and small business. In independence years this in the regions in the field done being increased reforms results, achievements and problems historical in aspect analysis done.